Web-Based Short Video Intervention and Short Message Comparison of Repeat Blood Donation Behavior Based on an Extended Theory of Planned Behavior: Prospective Randomized Controlled Trial Study - Qiuyue Hu; Wei Hu; Wenjuan Han; Lingling Pan (JMIR Publications, 2022)
BackgroundAlthough blood is an indispensable and important resource for clinical treatment, an imbalance between supply and demand may occur as the population ages and diversifies. Studies indicate that repeat blood donors are safe blood sources because of their voluntary blood donation education and frequent blood screening. However, the high rate of reduction in the number of first-time voluntary blood donors and low rate of repeated blood donation are common problems worldwide. ObjectiveThis study aimed to evaluate the effect of an intervention in nonregular blood donors using web-based videos and SMS text messages, in which the former was guided by the extended theory of planned behavior, to discover effective intervention methods to improve repeat blood donation rates among nonregular blood donors. MethodsA total of 692 nonregular blood donors in Zhejiang province were randomly divided into intervention and control groups. The control group received regular, short reminder messages for a 6-month period, whereas the intervention group received web-based videos on the WeChat platform. The intervention group was guided by an extended theory of planned behavior, which included 9 factors: the respondents' attitude, subjective behavioral norms, perceived behavioral control, the willingness to donate blood, outcome expectations, self-identity, blood donation-related anxiety, cognition of the blood donation environment, and previous blood donation experience. The intervention group was divided into 2 stages: those with an intervention at 3 months and those with a follow-up 3 months later. After 6 months, the redonation rate was evaluated for the 2 groups, and the scale in the intervention group was determined both before and after the intervention. A t test, chi-square test, logistic stepwise regression, and ANOVA were performed. ResultsThe intervention group's redonation rate was 16.14%, which was significantly higher than the control group's redonation rate of 5.16%; P<.001. Men who were aged 31 to 45 years and had donated blood twice had a higher redonation rate after the web-based video intervention than after the SMS text messages; P<.05. The repeat donors' improved blood donation anxiety (P=.01), outcome expectations (P=.008), and cognition of the blood donation environment (P=.005) after the intervention were significantly higher than those of the nonrepeat donors. ConclusionsThe web-based short video intervention based on the extended theory of planned behavior can effectively improve redonation rates. Outcome expectations, blood donation anxiety, and cognition of the blood donation environment can directly influence irregular blood donors to redonate blood.